Impaired Cerebral Vasoreactivity Despite Symptom Resolution in Sports-Related Concussion - Purkayastha, Sushmita (J Neurotrauma, 2019)
Traumatic brain injury (TBI) is associated with increased risk of later-life neurodegeneration and dementia. However, the underpinning mechanisms are poorly understood, and secondary injury resulting from perturbed physiological processes plays a significant role. Cerebral vasoreactivity (CVR), a measure of hemodynamic reserve, is known to be impaired in TBI. However, the temporal course of this physiological perturbation is not established. We examined CVR and clinical symptoms on day 3 (T1), day 21 (T2), and day 90 (T3) after concussion in collegiate athletes and cross-sectionally in non-injured controls. Changes in middle cerebral artery blood flow velocity (MCAV; transcranial Doppler ultrasonography) were measured during changes in end-tidal CO(2) (PetCO(2)) at normocapnia, hypercapnia (inspiring 8% CO(2)), and hypocapnia (hyperventilation). CVR was determined as the slope of the linear relationship and expressed as percent change in MCAV per mmHg change in PetCO(2). CVR was attenuated during the acute phase T1 (1.8 ± 0.4U; p = 0.0001), subacute phases T2 (2.0 ± 0.4U; p = 0.0017), and T3 (1.9 ± 0.6U; p = 0.023) post-concussion compared to the controls (2.3 ± 0.3U). Concussed athletes exhibited higher symptom number (2.5 ± 3.0 vs. 12.1 ± 7.0; p < 0.0001) and severity (4.2 ± 6.0 vs. 29.5 ± 23.0; p < 0.0001), higher Patient Health Questionnaire-9 score (2.2 ± 2.0 vs. 9.1 ± 6.0; p = 0.0003) at T1. However, by T2, symptoms had resolved. We show that CVR is impaired as early as 4 days and remains impaired up to 3 months post-injury despite symptom resolution. Persistent perturbations in CVR may therefore be involved in secondary injury. Future studies with a larger sample size and longer follow-up period are needed to validate this finding and delineate the duration of this vulnerable period.